Stability Analysis and Instability Time Prediction of Tunnel Roofs in a Karst Region Based on Catastrophe Theory - Yang Zou; Qianlong Tang; Limin Peng (Applied Sciences)
In order to address the safety construction issues of tunnels in karst areas, this study investigated the stability and instability time prediction of the roof of karst tunnels based on catastrophe theory. By establishing a discrimination equation for the sudden instability of the tunnel roof arch based on the elastic beam model and considering factors such as the self-weight of surrounding rocks and the position of caves, the calculation formula for the safety thickness of the roof of the karst tunnel was obtained. The study analyzed the impact of relevant factors on the safety thickness of the roof. Furthermore, a new method for predicting the instability of the tunnel roof arch was proposed, and it was validated through engineering examples. The results indicate that the water pressure in caves, the size of caves, the elasticity modulus of surrounding rocks, and the position of caves have extremely adverse effects on the safety of the arch roof. The calculation formula for the safety thickness of the roof of the karst tunnel derived from the theory of sudden change demonstrates feasibility and high accuracy in practical engineering applications. The established model for predicting roof instability can effectively forecast the time of roof arch instability in karst tunnels.